2014
DOI: 10.1155/2014/608927
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice of Hand Hygiene among Medical and Nursing Students at a Tertiary Health Care Centre in Raichur, India

Abstract: Background. Hand hygiene is recognized as the leading measure to prevent cross-transmission of microorganisms. Regarding hospital acquired infections, the compliance of nurses with hand washing guidelines seems to be vital in preventing the disease transmission among patients. There is a paucity of studies exploring this subject in Asia. Especially medical and nursing student's knowledge of standard hand hygiene precautions is rarely compared. Methods. A cross-sectional study was conducted among 98 medical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
181
9
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(222 citation statements)
references
References 11 publications
24
181
9
8
Order By: Relevance
“…This finding reveals a better scenario in the context of our country as a similar study conducted in Raichur, India reported that majority of the students had poor attitude towards hand hygiene. 12 In our study 20% of the participants felt that they didn't have sufficient knowledge on hand hygiene. This explains the need to conduct the training sessions to emphasize on the techniques and importance of hand hygiene prior to their hospital postings.…”
Section: Discussionmentioning
confidence: 58%
“…This finding reveals a better scenario in the context of our country as a similar study conducted in Raichur, India reported that majority of the students had poor attitude towards hand hygiene. 12 In our study 20% of the participants felt that they didn't have sufficient knowledge on hand hygiene. This explains the need to conduct the training sessions to emphasize on the techniques and importance of hand hygiene prior to their hospital postings.…”
Section: Discussionmentioning
confidence: 58%
“…15 This is on the contrary to Sreejith, Ramesh, Shashidhar, Mohammed and Pooja findings. 16 Their study showed that 74% of the students had moderate knowledge on hand hygiene and only 9% had good knowledge which were good findings. This moderate knowledge level would be explained in that the medical students received formal training on hand hygiene.…”
Section: Discussionmentioning
confidence: 96%
“…This is on the contrary to a study by Sreejith, Ramesh, Shashidhar, Mohammed and Pooja which findings showed that majority of the students had poor attitude with regard to hand hygiene. 16 From the highlighted barriers, there is a clear indication that social environmental factors influences the medical students hand hygiene practice as indicated by Bandura in his social cognitive theory which explains beyond the individual factors to other factors (environmental and social) that shapes human behaviour. 17 In reference to hand hygiene barriers, Al-Naggar and Al-Jashamy in their study majority of the participant mentioned laziness as the major and leading barrier to hand washing practice which was followed by lack of nearby water supply and a feeling that their hands were not dirty enough to get infected.…”
Section: Discussionmentioning
confidence: 99%
“…The literature survey suggests that commonly used hand rubs can eliminate common nosocomial pathogens such as Escherichia coli (most frequent cause of catheter associated urinary tract infection), Pseudomonas aeruginosa (cause of ventilator associated pneumonia), Staphylococcus aureus (most frequent cause of surgical site infection), and Staphylococcus epidermidis (most frequent cause of catheter associated bloodstream infection) [2]. Studies done in medical and nursing students in Sri Lanka and India show less compliance toward standard hand hygiene devised by the World Health Organization (WHO) [3,4]. Microbial flora was found to be high in those who use rings hence implying that wearing hand jewels is a risk factor for contamination [5].…”
Section: Introductionmentioning
confidence: 99%